2015
DOI: 10.2495/ess140231
|View full text |Cite
|
Sign up to set email alerts
|

Swarm intelligence based State-of-Charge optimization for charging Plug-in Hybrid Electric Vehicles

Abstract: Transportation electrification has undergone major changes since the last decade. Success of the smart grid with renewable energy integration solely depends upon the large-scale penetration of Plug-in Hybrid Electric Vehicles (PHEVs) for a sustainable and carbon-free transportation sector. One of the key performance indicators in the hybrid electric vehicle is the State-of-Charge (SoC), which needs to be optimized for the betterment of charging infrastructure using stochastic computational methods. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…PSO also has the capability of dealing with integer variables [14,21] and is widely used in intelligent sizing and multi-objective optimization in the automotive industry [21][22][23][24][25][26]. In order to accelerate PSO's convergence property, accelerated particle swarm optimization (APSO) is proposed, and evidences have showed that optimizing HEV with standard APSO outperforms the one with PSO [27,28]. Nevertheless, in real engineering practice, similar to most metaheuristic methods, APSO algorithm sometimes forces the agents to fall into local optima instead of global optima.…”
Section: Introductionmentioning
confidence: 99%
“…PSO also has the capability of dealing with integer variables [14,21] and is widely used in intelligent sizing and multi-objective optimization in the automotive industry [21][22][23][24][25][26]. In order to accelerate PSO's convergence property, accelerated particle swarm optimization (APSO) is proposed, and evidences have showed that optimizing HEV with standard APSO outperforms the one with PSO [27,28]. Nevertheless, in real engineering practice, similar to most metaheuristic methods, APSO algorithm sometimes forces the agents to fall into local optima instead of global optima.…”
Section: Introductionmentioning
confidence: 99%